Hubungan Pengetahuan terhadap Praktik Keamanan Pangan Pelaku Usaha UMKM - Ardianto, Muhammad; Suandi, Suandi; Nurhayati, Nurhayati (Jurnal Akademika Baiturrahim Jambi, 2024)
Aspects that need to be considered in achieving consumer satisfaction include food safety, quality and food and service in food administration. Food is a basic human need that must be considered for its taste and appearance as well as its safety for consumption. The potential for food to be contaminated with hazardous substances and become a source of disease transmission increases if the handling process until it is consumed by the community does not pay attention to hygiene and sanitation. The general objective of this study is to analyze the relationship between knowledge and attitudes towards food safety practices of UMKM business actors in the district. Jambi City Service. This research is a quantitative research with an observational approach and cross-sectional design. The study was conducted in March-May 2022 with a sample of 65 UMKM business actors who also act as food handlers. From the results of the analysis in this study, it was found that there was a significant relationship between knowledge of food safety practices of UMKM business actors in the District ofServant, which was marked with a significant value of p = 0.048